Gene therapy for inherited retinal and optic nerve degenerations - Nicholas Moore; Núria Morral; Thomas A. Ciulla; Peter Bracha (2017)
Introduction: The eye is a target for investigational gene therapy due to the monogenic nature of many inherited retinal and optic nerve degenerations (IRD), its accessibility, tight blood-ocular barrier, the ability to non-invasively monitor for functional and anatomic outcomes, as well as its relative immune privileged state.Vectors currently used in IRD clinical trials include adeno-associated virus (AAV), small single-stranded DNA viruses, and lentivirus, RNA viruses of the retrovirus family. Both can transduce non-dividing cells, but AAV are non-integrating, while lentivirus integrate into the host cell genome, and have a larger transgene capacity.Areas covered: This review covers Leber's congenital amaurosis, choroideremia, retinitis pigmentosa, Usher syndrome, Stargardt disease, Leber's hereditary optic neuropathy, Achromatopsia, and X-linked retinoschisis.Expert opinion: Despite great potential, gene therapy for IRD raises many questions, including the potential for less invasive intravitreal versus subretinal delivery, efficacy, safety, and longevity of response, as well as acceptance of novel study endpoints by regulatory bodies, patients, clinicians, and payers. Also, ultimate adoption of gene therapy for IRD will require widespread genetic screening to identify and diagnose patients based on genotype instead of phenotype.